Legal Analysis of Land Dispute Resolution Based on Alternative Dispute Resolution (ADR) - Juliaya Maria; Junaidi Lubis; M Salim (International Journal For Advanced Research, 2025)
This study explores the legal dimensions of resolving land disputes through Alternative Dispute Resolution (ADR) in Indonesia. Land disputes remain a persistent problem in the country, often caused by overlapping land claims, unclear land titles, and conflicting interests between communities, corporations, and government entities. Litigation processes are frequently prolonged and costly, which emphasizes the need for effective alternatives. This research aims to analyze how ADR can serve as a viable and just solution by examining its practical application, legal foundation, and societal impact. Using a qualitative approach supported by empirical data from interviews, case studies, and regulatory reviews, this study finds that ADR mechanisms—particularly mediation and negotiation—are capable of offering faster and more flexible dispute resolution compared to litigation. ADR also enables the inclusion of customary values and local wisdom, which is essential in regions where land ownership is deeply tied to tradition and community identity. However, the study also identifies major obstacles, including inconsistent regulatory support, lack of trained mediators, and limited access in rural areas. To maximize ADR’s effectiveness, the study recommends regulatory reform that specifically addresses land-related ADR, greater governmental and non-governmental support in ADR implementation, and public education to improve understanding and trust in these mechanisms. By strengthening ADR frameworks, Indonesia can create a more accessible and culturally responsive system of justice for land disputes. This research contributes to the broader discourse on legal reform and sustainable conflict resolution within the agrarian sector.